Influence of wide-aperture rotating gliding discharge on sunflower seed germination - Nedybaliuk, O.A.; Mordvintseva, L.Iu.; Fedirchyk, I.I.; Maruschak, M.S.; Chernolutsky, D.L. (Problems of Atomic Science and Technology, 2022)
The results of the study of the influence of wide-aperture rotating gliding discharge on the germination of sunflower seeds under different conditions are presented. The emission spectra of the plasma torch of DC wideaperture rotating gliding discharge are investigated. Vibrational Tv and rotational Tr temperatures of plasma inside the torch at the outlet of the discharge chamber were determined. The dependences of the percentage of germination of sunflower seeds germinated under favourable (sufficient amount of sunlight) and unfavourable conditions (insufficient amount of sunlight) on the 10th and 20th day after planting at different time intervals of treatment with a wide-aperture rotating gliding discharge were investigated. The optimal treatment time was determined.